A decision-making framework for aligning business analytics with business objectives - Sebe, Antoine (My University, 2020)
Throughout this thesis, we discuss the impact of Business Analytics on the organizational decision-making process with the objective of designing a framework that provides the organization with extra-knowledge on how to implement and sustain their analytics. First, we develop the concept of capability using the resource-based view and the IT literature to define what is a Business Analytics capability. We then define the key capabilities that provide the organization with a competitive advantage. Moreover, we investigate the role of governance and alignment as well as the impact of the concepts on the decision making effectiveness. To provide an insight on the adjustment to be made in order to increase the organization Business Analytics performance, we emphasise the role of alignment between Information Technology governance, corporate governance, data governance and Business Analytics governance. Thereafter we create the framework based on academic and empirical research and apply this framework throughout a case study. Based on this case study we provide an academic recommendation to the investigated organization. This thesis highlights the importance of the creation of a Business Analytics governance. Also, the research provides a framework linking Business Analytics with decision making successfulness.